Requirements Risk Management for Continuous Development : Organisational Needs - Kainulainen, Sanna; Tuunanen, Tuure; Vartiainen, Tero (Australasian Association for Information Systems, 2024)
Information systems development has recently evolved from traditional to agile and continuous forms. Continuous development (CD) methods, such as development and operations (DevOps), integrate many well-regarded parts of agile development and add collaboration among an organisation’s development, operations and quality assessment departments. We argue that requirements risk management (RRM) poses additional challenges to projects where development work is carried out quickly and continuously. However, in the literature, most methods for prioritising requirements and managing risks are more suited to traditional development. This raises the need for new tools and methodologies to meet CD challenges. As these challenges constantly evolve, project management must be able to control CD, changes in the determination of requirements and the accompanying risks. Based on a systematic literature review, we define the key features of CD and develop a conceptual three-dimensional framework that can be used to understand the organisational needs of RRM for CD.
Keywords: requirement risk management; agile; continuous development; development and operations; DevOps; systematic literature review; fi=Tietojärjestelmätiede|en=Information Systems|